The Activity Screening of Hmong Herbs Caesalpiniaminax and an Antitumor Effect Study. (26th October 2020) - Huang, Cong; Dong, Minghong; Luo, Jinfang; Qian, Haibing; Zhang, Jingjie; Huang, Yongqi
Abstract : Aim . To screen active sites from roots, stems, and leaves of Caesalpinia minax and study its antitumor effect. Methods . Human liver cancer HuH-7 cells were used to screen the active sites of C . minax by MTT assay, and the polar extracts were analyzed by high-performance liquid chromatography (HPLC). The medicated serum prepared from rats was used to investigate the effect on the proliferation of Hepa 1–6 mouse hepatoma cells. The H22 hepatoma-bearing mice model was established and treated with the petroleum ether extract of stems and leaves (HY②) by intraperitoneal injection (20, 60 mg·kg −1 ) and intragastric (100, 300 mg·kg −1 ) for 12 days. Results . The petroleum ether extracts were the effective active site. The IC50 value of the petroleum ether extract of stems and leaves (HY②) was 58.9 μ g·ml −1, and that of the roots (HG②) was 46.79 μ g·ml −1 . The grey relational analysis cleared that the 11 common peaks of the active extracts had a close correlation with the antitumor activity. The medicated serum prepared by ip. administration had a significant inhibitory effect on the Hepa1-6 cells, but it had no inhibitory effect by intragastric administration. High-dose administration significantly reduced tumor size in H22 hepatoma-bearing mice, and the tumor inhibition rates were 64.47% and 53.41%. Necrosis of tumor cells, infiltration of inflammatory cells, and fibrous tissue proliferation were promoted, and the expression of the proliferating cell nuclear antigen (PCNA) and vascular endothelial growth factor (VEGF) was reduced compared with the control group. Conclusion . The petroleum ether extract of C . minax had a significant antitumor activity. An immunohistochemical study showed that, through inhibiting the expression of the VEGF and growth of the tumor blood vessel, the proliferation of tumor cell and expression of PCNA can be inhibited.